INVESTIGATIONS ON THE CRIMINAL ACTION OF THE ABUSE OF NARCOTICS OF THE TYPE OF SHABU IN ADOLESCENTS BASED ON THE REGULATION OF THE HEAD OF POLICE NUMBER 6 OF 2019: PENYIDIKAN TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA JENIS SHABU PADA REMAJA BERDASARKAN PERATURAN KEPALA KEPOLISIAN NOMOR 6 TAHUN 2019 - Napitupulu, JM Gabe (LPPM UPMI, 2023)
Investigation is an initial process of completing a crime that needs to be thoroughly investigated and investigated within the criminal justice system. The most dangerous crime among adolescents is the abuse of methamphetamine. The type of research in this paper is normative with a statutory and conceptual approach. The research specification is analytical descriptive while the data used is secondary data which consists of primary legal material in the form of statutory regulations, namely the Criminal Code, Police Chief Regulation Number 6 of 2019 concerning Investigation of Criminal Acts. and secondary legal materials in the form of books, journals and writings related to the research title. The data analysis method was carried out qualitatively. The implementation of investigations into criminal acts of narcotics abuse in adolescents based on Police Chief Regulation Number 6 of 2019 must pay attention to and be guided by Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In its implementation, it prioritizes restorative justice efforts. For this reason, it is suggested that the investigator understand more about the Regulation of the Chief of Police Number 6 of 2019.